GEOGRAPHICAL ENVIRONMENT CONDITIONS, RURAL SETTLEMENTS AND ECONOMIC ACTIVITIES IN ÇAYBAGI RIVER’S BASIN (SARAY/VAN): PROBLEMS AND SUGGESTIONS - Murat YILMAZ (Fırat University, 2019)
The purpose of this study is to examine geographical environment, rural settlements and economic activities in Çaybağı River Basin. Çaybağı River Basin is located east part of Turkey. It is located in the administrative area of the Saray District of Van Province. In the research area, currently, there are 23 rural settlements including 2 hamlets 21 villages and the population in these settlements are 15684. The geographical characteristics of settlements in the Çaybağı River Basin vary from each other. The mountainous places, slope, the bank of the lake and riverside places, foothills, plain areas, are selected as settlement places. In the research area, all the village settlements are collective textured. Altitude of the settlement in the area is quite high and so are the upper and lower limits which are respectively 2050 and 2450 meters. In the study area, average village population is 755 and population of the villages vary between 190 and 2057. In the basin area, the average acreage of the villages is 2746 hectare while acreage varies among 842,7 hectare and 5788,2 hectare. The old and the new names of the villages in Basin have marks of the physical and human geography of the area. In the study area, main economic activities of villagers are agriculture and livestock. People from the region continue to migrate outwards because of limited livelihoods. Agriculture and livestock need to be done by more efficient methods to reduce migration from the region. Also, it is necessary to develop alternative livelihoods such as livestock, beekeeping and aquaculture which have potentials in the region.